Identitas Kota Sawahlunto Paska Kejayaan Pertambangan Batu Bara - Suprayoga, Gede Budi (Journal of Regional and City Planning, 2008)
The City of Sawahlunto was previously recognized by its coal mining activities. Since the decline of mining production in Sawahlunto, the city became a new administrative area which is divided into old and new town areas. This paper discusses the changing identity of Sawahlunto. Urban involution characterizes the town condition; the population number increases but without the expansion of urban character. Some parts of the town are small settlements with strong local identity. Thus, this condition affects âthe breakdownâ or âthe dualityâ of Sawahlunto identity represented by old town and Talawi city.Keywords:Â town, Sawahlunto, mining, colonial town, identity, local, urban involution, Talawi